Analisis Determinan Perilaku Terhdap Kejadian Demam Berdarah Dengue (DBD) di Wilayah Kerja Puskesmas Ambawara - Ita Puji Lestari; Kartika Dian Pertiwi; Fiki Wijayanti (Pro Health Jurnal Ilmiah Kesehatan, 2021)
Dengue fever is a disease caused by dengue virus transmitted to humans by the aedes aegypti mosquito bite and aedes albocpictus.Risk factors of dengue fever among others used to hang clothes or clothing, have scattered trash around the house.The purpose of this research analyze determinan behavior covering knowledge, attitude, and practices the prevention of dengue fever in the work area of puskesmas ambarawa kabupaten semarang.Research methodology this is what in use descriptive namely research of observational with cross sectiona approachment. Respondents are 63 people.A measuring instrument that in use that is the questionnaire and the result used analysis univariat.The results of the study there were respondents to the level of knowledge of good 20 people ( 31.7 % ), the seizing of the 24 enough knowledge ( 38,1 % ), and penegahuan less 19 ( 30.2 % ).Respondents who have good category 12 people ( while 20.6 % ), enough 7 people ( 11.1 % ) and category less 43 people ( 68.3 % )respondents. Suggested on the community can be more active in behaving in the prevention of dengue fever, as do the programs in reducing, and mosquito nest eradication.